Learning Media Development National Movement History Comics Indonesia's Main Material Development Ideology and Organization Movement Indonesian National for Students Class XI IPS SMA N 1 Bobotsari - Pangestika, Permata Ajeng (Indonesian Journal of History Education, 2019)
This study aims to determine the needs of teachers and students for instructional media in the form of comics. As a research and development (R&D) study, it followed several stages: identifying potential problems, collecting data, designing the product, validating it with experts, making revisions, and conducting product trials. The instructional media, specifically a comic about the history of the Indonesian National Movement, was developed using Photoshop CS6 and CorelDraw X7 to combine visual elements effectively. The validation results from experts indicated that this comic-based instructional media is suitable for use as a learning tool. The study's findings revealed that current school learning resources primarily consist of textbooks and worksheets, which are often presented less engagingly, leading to student boredom. Although PowerPoint presentations are used, their application is still limited, highlighting the need for more practical, innovative, and creative instructional media. The introduction of the comic-based history learning media received a positive response from students during trials, suggesting that such media could enhance engagement and make learning more enjoyable.